Carbon-oxygen corrosion resistant coating powder material and preparation method of carbon-oxygen corrosion resistant coating
By applying a specific coating powder material and laser cladding process on supercritical CO2 hot-end equipment, a coating that is resistant to carbon-oxygen corrosion is solved, and the equipment corrosion problem is significantly improved. Lifespan and safety.
Patent Information
- Application Number
- CN202411645412.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
AI Technical Summary
Supercritical CO2 hot-end equipment materials are prone to carbon-oxygen corrosion in high-temperature and high-pressure environments, which affects the service life of the equipment and may cause safety accidents.
A coating powder material that is resistant to carbon-oxygen corrosion is used, and the chemical composition is: 21-24 wt.% Cr, 7-10 wt.% Mo, 3-5 wt.% Nb, 2-4 wt.% Co, 1-2 wt. %W, 0.4-0.7wt.%Ti, 0.1-0.3wt.%Si and 0.05-0.10wt.%B, the balance is Ni, and it is prepared by water mist method and a laser cladding process is used to form carbon resistance on the surface of the equipment substrate. - High-quality coating for oxygen corrosion.
It significantly improves the performance and effective operating life of metal components, enhances the strength, thermal stability and oxidation resistance of the carbon-oxygen corrosion coating, reduces the friction coefficient and energy loss of the equipment, and improves working efficiency.
Smart Images

Figure CN119464845A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of advanced materials, and specifically discloses a coating powder material resistant to carbon-oxygen corrosion and a preparation method of the coating resistant to carbon-oxygen corrosion. Background Art
[0002] Supercritical fluids are often used as coolants in power plants due to their efficient heat transfer capabilities and good fluidity. 2 When the temperature and pressure exceed 31.1℃ and 7.39MPa respectively, it turns into supercritical fluid, which is a promising working fluid for thermoelectric conversion system of nuclear power, fossil energy and solar power plants. 2 The Brayton cycle is a thermodynamic cycle mainly used in gas turbines and aircraft engines. It consists of four main processes: isobaric heating, isenthalpic expansion, isobaric cooling and isenthalpic compression. 2 The efficiency of the Brayton cycle (up to 50%) is significantly higher than the current standard steam Rankine cycle, and will have a wide-ranging impact on the power industry in terms of reducing carbon emissions, reducing the demand for fossil fuel extraction and lowering electricity costs.
[0003] In the critical region CO 2 The drastic change in physical properties leads to a reduction in system compression work, a relatively compact system structure, and thus improved cycle efficiency. 2 Large-scale application of the Brayton cycle still faces many problems. For example, when the hot-end equipment is in operation, it will be in a high-temperature and high-pressure environment for a long time and be affected by large thermal stress, which will cause serious problems such as carbon-oxygen corrosion, affecting the service life of the equipment and even causing safety accidents such as leakage and explosion. 2 The engineering application of the Brayton cycle urgently needs to solve the problem of supercritical CO 2 The problem of carbon-oxygen corrosion resistance of hot end equipment materials. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of supercritical CO 2 In order to solve the carbon-oxygen corrosion problem of hot end equipment materials, a carbon-oxygen corrosion-resistant coating powder material and a preparation method of a carbon-oxygen corrosion-resistant coating are proposed. The carbon-oxygen corrosion-resistant coating powder material is clad in supercritical CO 2 A high-quality coating that resists carbon-oxygen corrosion is formed on the surface of the hot end equipment substrate, thereby improving the performance and effective operating life of metal components.
[0005] In order to solve the above technical problems, the present invention provides a coating powder material resistant to carbon-oxygen corrosion, whose chemical composition is: 21-24wt.% Cr, 7-10wt.% Mo, 3-5wt.% Nb, 2-4wt.% Co, 1-2wt.% W, 0.4-0.7wt.% Ti, 0.1-0.3wt.% Si and 0.05-0.10wt.% B, and the balance is Ni.
[0006] As a further description of the present invention, the particle size of the coating powder material is 16 μm to 54 μm.
[0007] As a further description of the present invention, the coating powder material is prepared by a water mist method, specifically: electrolytic Ni powder, Cr powder, Mo powder, Nb powder, Co powder, W powder, Si powder, and B powder are used as raw materials, the raw materials are proportioned according to a ratio, and placed in a medium frequency induction furnace for smelting and melting, the melt temperature is 1550°C, the molten metal liquid is transitioned from the tundish into the atomization zone, and is broken into metal droplets by high-pressure atomized water, and rapidly cooled and solidified into powder, the obtained atomized powder is then separated by water and powder, the powder is dried in a vacuum dryer, and finally the powder is graded to select a powder particle size within the range of 16μm to 54μm, and finally the coating powder material resistant to carbon-oxygen corrosion of the present invention is obtained. In order to reduce alloy oxidation and reduce production costs, Ar gas is used as a protective atmosphere during the alloy smelting process.
[0008] The coating powder material of the present invention adopts Ni-based components as the matrix phase, and is prepared according to supercritical CO 2 The content of each component of the coating powder material is optimized according to the actual service conditions of the hot end equipment.
[0009] The coating powder material of the present invention uses Ni-based components as the matrix phase, which has the following advantages: moderate cost and is suitable for large-scale use; has excellent wear resistance and can effectively protect the surface of the substrate from wear; has good corrosion resistance and can extend the service life of the substrate; can significantly improve the hardness of the substrate surface and increase its wear resistance; can reduce the friction coefficient of the substrate surface, reduce energy loss, and improve work efficiency.
[0010] The addition of Cr element to the coating powder material of the present invention has important effects mainly in the following aspects: compared with the material steam oxidation in the supercritical steam Rankine cycle, the supercritical CO 2 Heat-resistant materials in the environment will be carburized. The corrosion mechanism changes from the traditional oxidation mechanism to the oxidation and carburization coupling mechanism. At the same time, because the radius of oxygen ions is much larger than that of carbon ions, the diffusion pathways and rates of their ions are different. The C that penetrates into the matrix combines with the corrosion-resistant element Cr to form carbides, reducing the content of mobile Cr. Sufficient Cr content can promote the Cr on the surface of the material. 2 O3 The formation of oxide film, Cr 2 O 3 The oxide film can prevent the penetration of C. In addition, the Cr element can improve the thermal stability of the coating, so that it can still maintain good performance in high temperature environment.
[0011] The addition of Mo element to the coating powder material of the present invention mainly has the following effects: Mo element can significantly improve the strength and thermal strength of the carbon-oxygen corrosion resistant coating. In a high temperature environment, Mo can form stable carbides, and these carbides can enhance the creep strength and endurance strength of the carbon-oxygen corrosion resistant coating, thereby maintaining better performance at high temperatures; the addition of Mo element can effectively inhibit the occurrence of plastic deformation phenomenon that occurs when the carbon-oxygen corrosion resistant coating is subjected to stress for a long time at high temperature, thereby improving the creep resistance of the carbon-oxygen corrosion resistant coating at high temperatures; Mo and other elements (such as niobium Nb) synergistically form stable carbides, further enhancing the creep strength and endurance strength of the carbon-oxygen corrosion resistant coating. These carbides can also improve the thermal stability of the carbon-oxygen corrosion resistant coating, so that it maintains better performance at high temperatures.
[0012] Nb element is added to the coating powder material of the present invention. The main effects of Nb element include solid solution strengthening and precipitation strengthening. Nb mainly forms phases such as NbC, which can improve the creep strength of the carbon-oxygen corrosion resistant coating, reduce the creep rate, and ensure good laser cladding process performance of the carbon-oxygen corrosion resistant coating. Nb and other alloy elements in the coating, such as Ni and Ti elements, can interact to form γ'-Ni3Ti phase, γ"-Ni3Nb phase, δ-Ni3Nb phase, ε-Ni3(Nb,Ti) phase, etc. By controlling the size, morphology and distribution of the precipitated phases, these phases can enable the coating to obtain good comprehensive performance.
[0013] Co element is added to the coating powder material of the present invention. The functions of the Co element mainly include improving the thermal stability and high-temperature strength of the alloy. Co can enhance the stability of the carbon-oxygen corrosion resistant coating in a high-temperature environment, so that it can still maintain good mechanical properties under extreme conditions; in a high-temperature working environment, Co can effectively improve the strength of the carbon-oxygen corrosion resistant coating, ensuring that the carbon-oxygen corrosion resistant coating can still maintain sufficient strength and hardness under extreme conditions; Co can form a good metallurgical bond with the base metal, and improve the bonding strength between the coating and the base; Co can prevent the diffusion of some harmful elements such as oxygen and sulfur in the coating, and improve the anti-oxidation and anti-corrosion properties of the coating.
[0014] The coating powder material of the present invention adds W element. W is one of the important strengthening elements in high temperature alloys, which can significantly improve the high temperature strength of the carbon-oxygen corrosion resistant coating. After W enters the γ matrix, lattice distortion will occur, which helps to hinder dislocation movement, thereby improving the strength and hardness of the carbon-oxygen corrosion resistant coating. Lattice distortion will also cause the γ′ / γ mismatch to decrease, further affecting the performance of the carbon-oxygen corrosion resistant coating; W has an extremely high melting point (3422°C) and excellent thermal stability, which can improve the coating's oxidation resistance and thermal corrosion resistance in high temperature environments; W can form stable compounds with other elements to improve the corrosion resistance of the coating in corrosive environments such as acids and alkalis.
[0015] The coating powder material of the present invention adds Ti element, which can form strong TiC. This compound can be stable to 1300°C and has a highly dispersed characteristic, thereby refining the grains and reducing the overheating tendency of the carbon-oxygen corrosion resistant coating. In addition, Ti can reduce the carbon-oxygen corrosion phenomenon of the coating, and the free carbon that penetrates deep into the coating at high temperature can be combined into strong TiC, thereby avoiding the formation of chromium carbide at the grain boundaries, and further reducing intergranular corrosion.
[0016] The coating powder material of the present invention adds Si element, and the oxide (such as SiO 2 ) has the characteristics of being dense and stable, which can effectively prevent the matrix elements from diffusing outward, thereby reducing the oxidation rate and improving the oxidation resistance of the carbon-oxygen corrosion resistant coating; in addition, Si oxide can form a dense oxide film at high temperature, which can prevent oxygen from further contacting the alloy and further enhance its oxidation resistance; Si element forms SiO 2 The layer improves the anti-carburization ability of the carbon-oxygen corrosion resistant coating.
[0017] The B element is added to the coating powder material of the present invention, and the B element can effectively improve the strength of the grain boundary in the carbon-oxygen corrosion resistant coating, thereby enhancing the high temperature performance and heat resistance of the carbon-oxygen corrosion resistant coating; the introduction of the B element can improve the oxidation resistance of the carbon-oxygen corrosion resistant coating, thereby extending its service life; an appropriate amount of the B element can improve the strength and ductility of the carbon-oxygen corrosion resistant coating, especially when serving at high temperatures.
[0018] In order to solve the above technical problems, the present invention also provides a method for preparing a carbon-oxygen corrosion resistant coating, comprising: using a laser cladding process to form a coating on the surface of a substrate using the above coating powder material.
[0019] As a further description of the present invention, the laser power of the laser cladding process is 4000-5000W, the scanning speed is 800-1000mm / min, the laser spot size is 5mm, and the powder feeding rate of the powder feeder is 5-7r / min.
[0020] As a further description of the present invention, the welding overlap rate of the laser cladding process is 30%.
[0021] As a further description of the present invention, the protective gas of the laser cladding process is Ar gas, and the protective gas flow rate is 15 to 20 L / min.
[0022] As a further description of the present invention, the method for preparing the carbon-oxygen corrosion resistant coating further includes drying the coating powder material before the laser cladding operation.
[0023] As a further description of the present invention, the stacking thickness of the coating powder material during drying is ≤5 mm, the drying temperature is (80±2)° C., and the insulation time is 2 h.
[0024] As a further description of the present invention, the dried coating powder material should be dried again when it is placed in the air for more than 4 hours before being used.
[0025] The present invention uses surface engineering technology (laser cladding) to obtain a protective coating on the surface of the substrate that resists carbon-oxygen corrosion, greatly improving the supercritical CO 2 The surface hardness, corrosion resistance and wear resistance of the hot end equipment material. The carbon-oxygen corrosion resistant coating prepared by the present invention is a new type of carbon-oxygen corrosion resistant functional coating, with a coating thickness of 1.0 to 2 mm, a metallurgical bond between the coating and the substrate, a bonding strength of ≥400Mpa, a dense internal structure of the coating, a porosity of ≤1%, a statistical segregation of ≤0.06, no penetrating defects in the coating, a maximum size of micro-defects that can be healed of ≥200μm, and a residual compressive stress of ≥800MPa; the laser deposited layer is heated at 650℃ / 20MPa supercritical CO 2 Weight gain ≤ 0.03 mg / cm after 1000 h in static environment 2 、The weight change after 1000h in a high flow rate dynamic environment of 10m / s is ≤0.05mg / cm 2 , which can be used in the manufacturing of key components of energy equipment such as nuclear power. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a morphological photograph of the carbon-oxygen corrosion resistant coating prepared in Example 3;
[0027] Figure 2 is a microstructure photograph of the carbon-oxygen corrosion resistant coating prepared in Example 3;
[0028] Figure 3 This is a morphology photograph of the carbon-oxygen corrosion resistant coating prepared in Example 3 after the hot corrosion test. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0030] Embodiment 1:
[0031] This embodiment provides a coating powder material resistant to carbon-oxygen corrosion, whose chemical composition is: 21wt.% Cr, 10wt.% Mo, 4wt.% Nb, 2wt.% Co, 1.5wt.% W, 0.4wt.% Ti, 0.3wt.% Si and 0.08wt.% B, and the balance is Ni.
[0032] The coating powder material of this embodiment is prepared by a water mist method, specifically: electrolytic Ni powder, Cr powder, Mo powder, Nb powder, Co powder, W powder, Si powder, and B powder are used as raw materials, the raw materials are proportioned according to a certain ratio, and are placed in a medium frequency induction furnace for smelting and melting. The melt temperature is 1550°C. In order to reduce alloy oxidation and reduce production costs, Ar gas is used as a protective atmosphere in the alloy smelting process. After the molten metal liquid transitions from the tundish into the atomization zone, it is broken into metal droplets by high-pressure atomized water, and is rapidly cooled and solidified into powder. Subsequently, the obtained atomized powder is separated by water and powder, and the powder is dried in a vacuum dryer. Finally, the powder is graded and the powder particle size is selected within the range of 16μm to 54μm, and finally a coating powder material resistant to carbon-oxygen corrosion is obtained.
[0033] This embodiment also provides a method for preparing a carbon-oxygen corrosion resistant coating, comprising the following steps:
[0034] (1) Drying of coating powder materials: During drying, the accumulated thickness of coating powder materials should be ≤5mm, the drying temperature should be (80±2)℃, and the holding time should be 2h. Dried coating powder materials should be dried again if they are left in the air for more than 4h before being used;
[0035] (2) Laser cladding: The protective gas for laser cladding is Ar gas, the protective gas flow rate is 15 L / min, the laser power is 4000 W, the scanning speed is 900 mm / min, the laser spot size is 5 mm, the overlap rate is 30%, and the powder feeder powder feeding rate is 7 r / min.
[0036] The carbon-oxygen corrosion resistant coating manufactured in this embodiment has a coating thickness of 1.5 mm, a metallurgical bond between the coating and the substrate, a bonding strength of 450 MPa, a dense internal structure of the coating, a porosity of 0.05%, a statistical segregation of 0.04, no penetrating defects in the coating, a maximum size of healable micro-defects of 240 μm, and a residual compressive stress of 820 MPa; the laser deposited layer is heated at 650 ° C / 20 MPa supercritical CO 2 Weight gain after 1000h in static environment: 0.02mg / cm 2 , 10m / s high velocity dynamic environment after 1000h weight change 0.04mg / cm2 .
[0037] Embodiment 2:
[0038] This embodiment provides a coating powder material resistant to carbon-oxygen corrosion, whose chemical composition is: 24wt.% Cr, 8wt.% Mo, 3wt.% Nb, 3wt.% Co, 2wt.% W, 0.5wt.% Ti, 0.1wt.% Si and 0.05wt.% B, and the balance is Ni.
[0039] The coating powder material of this embodiment is prepared by a water mist method, specifically: electrolytic Ni powder, Cr powder, Mo powder, Nb powder, Co powder, W powder, Si powder, and B powder are used as raw materials, the raw materials are proportioned according to a certain ratio, and are placed in a medium frequency induction furnace for smelting and melting. The melt temperature is 1550°C. In order to reduce alloy oxidation and reduce production costs, Ar gas is used as a protective atmosphere in the alloy smelting process. After the molten metal liquid transitions from the tundish into the atomization zone, it is broken into metal droplets by high-pressure atomized water, and is rapidly cooled and solidified into powder. Subsequently, the obtained atomized powder is separated by water and powder, and the powder is dried in a vacuum dryer. Finally, the powder is graded and the powder particle size is selected within the range of 16μm to 54μm, and finally a coating powder material resistant to carbon-oxygen corrosion is obtained.
[0040] This embodiment also provides a method for preparing a carbon-oxygen corrosion resistant coating, comprising the following steps:
[0041] (3) Drying of coating powder materials: During drying, the accumulated thickness of coating powder materials should be ≤5mm, the drying temperature should be (80±2)℃, and the holding time should be 2h. Dried coating powder materials should be dried again if they are left in the air for more than 4h before being used;
[0042] (4) Laser cladding: The protective gas for laser cladding is Ar gas, the protective gas flow rate is 18 L / min, the laser power is 4500 W, the scanning speed is 800 mm / min, the laser spot size is 5 mm, the overlap rate is 30%, and the powder feeder powder feeding rate is 5 r / min.
[0043] The carbon-oxygen corrosion resistant coating manufactured in this embodiment has a coating thickness of 1.0 mm, a metallurgical bond between the coating and the substrate, a bonding strength of 480 MPa, a dense internal structure of the coating, a porosity of 0.04%, a statistical segregation of 0.05, no penetrating defects in the coating, a maximum size of healable micro-defects of 260 μm, and a residual compressive stress of 860 MPa; the laser deposited layer is heated at 650 ° C / 20 MPa supercritical CO 2 Weight gain after 1000h in static environment: 0.024mg / cm 2 , 10m / s high velocity dynamic environment after 1000h weight change 0.035mg / cm 2 .
[0044] Embodiment 3:
[0045] This embodiment provides a coating powder material resistant to carbon-oxygen corrosion, whose chemical composition is: 22wt.% Cr, 7wt.% Mo, 5wt.% Nb, 4wt.% Co, 1wt.% W, 0.7wt.% Ti, 0.2wt.% Si and 0.10wt.% B, and the balance is Ni.
[0046] The coating powder material of this embodiment is prepared by a water mist method, specifically: electrolytic Ni powder, Cr powder, Mo powder, Nb powder, Co powder, W powder, Si powder, and B powder are used as raw materials, the raw materials are proportioned according to a certain ratio, and are placed in a medium frequency induction furnace for smelting and melting. The melt temperature is 1550°C. In order to reduce alloy oxidation and reduce production costs, Ar gas is used as a protective atmosphere in the alloy smelting process. After the molten metal liquid transitions from the tundish into the atomization zone, it is broken into metal droplets by high-pressure atomized water, and is rapidly cooled and solidified into powder. Subsequently, the obtained atomized powder is separated by water and powder, and the powder is dried in a vacuum dryer. Finally, the powder is graded and the powder particle size is selected within the range of 16μm to 54μm, and finally a coating powder material resistant to carbon-oxygen corrosion is obtained.
[0047] This embodiment also provides a method for preparing a carbon-oxygen corrosion resistant coating, comprising the following steps:
[0048] (5) Drying of coating powder materials: During drying, the accumulated thickness of coating powder materials should be ≤5mm, the drying temperature should be (80±2)℃, and the holding time should be 2h. Dried coating powder materials should be dried again if they are left in the air for more than 4h before being used;
[0049] (6) Laser cladding: The protective gas for laser cladding is Ar gas, the protective gas flow rate is 20 L / min, the laser power is 5000 W, the scanning speed is 1000 mm / min, the laser spot size is 5 mm, the overlap rate is 30%, and the powder feeder powder feeding rate is 6 r / min.
[0050] The carbon-oxygen corrosion resistant coating manufactured in this embodiment has a coating thickness of 2.0 mm, a metallurgical bond between the coating and the substrate, a bonding strength of 500 MPa, a dense internal structure of the coating, a porosity of 0.03%, a statistical segregation of 0.044, no penetrating defects in the coating, a maximum size of healable micro-defects of 230 μm, and a residual compressive stress of 870 MPa; the laser deposited layer is heated at a supercritical CO temperature of 650 ° C / 20 MPa. 2 Weight gain after 1000h in static environment: 0.022mg / cm 2 , 10m / s high velocity dynamic environment after 1000h weight change 0.041mg / cm 2 .
[0051] from Figure 1 It can be seen that the coating is well formed; Figure 2 It can be seen that the coating is dense and almost defect-free. Figure 3 It can be seen that the coating has excellent anti-carbon-oxygen corrosion performance.
[0052] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. A person skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the present invention.
Claims
1. A coating powder material resistant to carbon-oxygen corrosion, characterized in that: Its chemical composition is: 21-24wt.% Cr, 7-10wt.% Mo, 3-5wt.% Nb, 2-4wt.% Co, 1-2wt.% W, 0.4-0.7wt.% Ti, 0.1-0.3wt.% Si and 0.05-0.10wt.% B, and the balance is Ni.
2. The coating powder material according to claim 1, characterized in that: The particle size of the coating powder material is 16 μm to 54 μm.
3. The coating powder material according to claim 1, characterized in that: The coating powder material is prepared by a water mist method.
4. A method for preparing a carbon-oxygen corrosion resistant coating, characterized in that: include: The coating powder material according to any one of claims 1 to 3 is formed into a coating on the surface of a substrate by using a laser cladding process.
5. The preparation method according to claim 4, characterized in that: The laser power of the laser cladding process is 4000-5000W, the scanning speed is 800-1000mm / min, the laser spot size is 5mm, and the powder feeding rate of the powder feeder is 5-7r / min.
6. The preparation method according to claim 4 or 5, characterized in that: The welding overlap rate of the laser cladding process is 30%.
7. The preparation method according to claim 6, characterized in that: The protective gas of the laser cladding process is Ar gas, and the protective gas flow rate is 15-20 L / min.
8. The preparation method according to claim 4, characterized in that: The method also includes drying the coating powder material before the laser cladding operation.
9. The preparation method according to claim 8, characterized in that: The stacking thickness of the coating powder material during drying is ≤5mm, the drying temperature is 78-82°C, and the insulation time is 2h.
Citation Information
Cited By
Alloy powder suitable for surface treatment of petroleum screw and application method of alloy powder
CN119710526A
Alloy powder suitable for oil screw surface treatment and application method thereof
CN119710526B